2017
DOI: 10.1530/joe-16-0669
|View full text |Cite
|
Sign up to set email alerts
|

30 YEARS OF THE MINERALOCORTICOID RECEPTOR: Mineralocorticoid receptor and NaCl transport mechanisms in the renal distal nephron

Abstract: A key role of aldosterone and mineralocorticoid receptor is to regulate fluid volume and K + homeostasis in the body by acting on the renal distal nephron. Global responses of the kidney to elevated aldosterone levels are determined by the coordinate action of different constituent tubule cells, including principal cells, intercalated cells and distal convoluted tubule cells. Recent studies on genetic mutations causing aldosterone overproduction have identified the molecules involved in aldosterone biosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 99 publications
1
39
0
Order By: Relevance
“…The preventive effects of PC on the HFD-induced basophilic tubules may be related to MR/ NOX signaling pathway (Whaley-Connell et al, 2010), since the basophilic tubules expressed MR and p22phox as demonstrated by immunohistochemistry. The immuno-positive reaction of MR in the cytoplasms and nuclei was confirmed in the distal tubules and collecting tubules in kidney sections, as reported previously (Lombès et al, 1990), and supporting the role of MR in sodium absorption and potassium retention by regulating Na-Cl cotransporter in these tubules (Shibata, 2017). The biological significance of nuclear localization of MR in basophilic tubules remains uncertain.…”
Section: Discussionsupporting
confidence: 85%
“…The preventive effects of PC on the HFD-induced basophilic tubules may be related to MR/ NOX signaling pathway (Whaley-Connell et al, 2010), since the basophilic tubules expressed MR and p22phox as demonstrated by immunohistochemistry. The immuno-positive reaction of MR in the cytoplasms and nuclei was confirmed in the distal tubules and collecting tubules in kidney sections, as reported previously (Lombès et al, 1990), and supporting the role of MR in sodium absorption and potassium retention by regulating Na-Cl cotransporter in these tubules (Shibata, 2017). The biological significance of nuclear localization of MR in basophilic tubules remains uncertain.…”
Section: Discussionsupporting
confidence: 85%
“…In mammals, in addition to aldosterone, the glucocorticoids are also a major ligand of MR; however, almost all the mineralocorticoid functions are mediated by aldosterone-MR signalling 5 . The high affinity of cortisol for MR means that aldosterone-mediated effects occur in tissues where 11β-hydroxysteroid dehydrogenase 2 (11β-HSD2), a key enzyme that breaks down cortisol, is prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…The encoded proteins are highly important in sodium reabsorption (epithelial Na + channel, ENaC) including the maintenance of sodium and potassium channels to the membrane (GILZ), and the maintenance of the mineralocorticoid signaling pathway (FKBP5 and USP2). 48 Aldosterone is known to promote inflammation in the kidney during CKD, through the promotion of macrophages infiltration and maturation. 49 At a systemic level, it also represses inflammation (interleukins) and favors fibrosis protein markers (CTGF, TGF-β2) directly in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%